Determination and validation of dispersive solid phase extraction and its application in determination of anthelmintics avermectins in fish - Ismail, Rafidah (2014)
Anthelmintics avermetcins are veterinary drugs used as anti-parasites in food producing animals. An analytical method which will yield fast and reliable results for the determination of avermectins in aquaculture fish is an essential to ensure compliance with food safety monitoring programmes. The following objectives are set in order to achieve the above goal: to investigate the effectiveness of octadecyl (C18), primary secondary amine (PSA) and alumina clean-up sorbents used in the Dispersive Solid Phase Extraction (d-SPE) procedure in determination of avermectins in barramundi (Lates calcarifer); to select the clean-up sorbent(s) which will give the highest recovery rate in the detection of avermectins; to validate the use of the selected clean-up sorbent(s) as well estimate the measurement uncertainties and to verify the effectiveness of the d-SPE method for the determination of avermectins in five aquaculture fish species. A total of five avermectin compounds is evaluated in this study, namely, emamectin, abamectin, doramectin, moxidectin and ivermectin. Homogenised barramundi (L. calcarifer) samples are extracted with acetonitrile and purified using the d-SPE procedure. The presence of avermectins in the samples were quantified using LC-MS/MS. It is found that the use of combined PSA and C18 sorbents at a ratio of 1:1 results in high recovery rates for all avermectins with a range of 94 – 103% and relative standard deviations (RSDs) less than 11%, compared to the use of individual sorbents. Hence, the combined PSA and C18 sorbents are selected for further analysis using the d-SPE method. Method validation has been carried out and the LOD within the range of 0.3 – 0.4 μg/kg, whereas the LOQ is 1 μg/kg. The linearity of the method is 1 – 15 μg/kg for all avermectins. The precision of the method is less than 20%, while the trueness of the method is within the range of 87 - 102% for low, medium and high concentration levels of 1, 2 and 5 μg/kg. The measurement uncertainty has been estimated. The use of the combined PSA and C18 sorbents with the d-SPE method has been verified to determine the presence of avermectins in five aquaculture fish species with dissimilar fatty acid content, namely, barramundi (L. calcarifer), tilapia (Oreochromis sp.), river catfish (Pangasius sp.), grouper (Epinephelus sp.) and snapper (Lutjanus sp.). A total of 34 fish samples are used for this purpose and the applicability of the d-SPE method has been demonstrated by the detection of emamectin in two fish samples, i.e. grouper (Epinephelus sp.) and snapper (Lutjanus sp.), which corresponds to 5.9%. Confirmatory analysis has been carried out and confirm that the emamectin residues are detected above the LOD but below the LOQ (1 μg/kg) for both samples. Based on the findings of this study, it is recommended that the d-SPE method is implemented as part of the veterinary residue monitoring plan in Malaysia in order to establish a comprehensive database on the use of avermectins in aquaculture fish.